A conserved motif is essential for the correct assembly of proglutelins and for their export from the endoplasmic reticulum in rice endosperm. (10th August 2018) - Tian, Lihong; Xing, Yanping; Fukuda, Masako; Li, Rong; Kumamaru, Toshihiro; Qian, Dandan; Dong, Xiangbai; Qu, Le Qing
Abstract : Characterization of a mutant that specifically accumulates the GluA precursor reveals a conserved motif in proglutelins that is essential for their proper assembly in, and their subsequent export from, the endoplasmic reticulum. Abstract: Rice glutelins are initially synthesized as 57-kDa precursors at the endoplasmic reticulum (ER) and are ultimately transported into protein storage vacuoles. However, the sequence motifs that affect proglutelin folding, assembly, and their export from the ER remain poorly defined. In this study, we characterized a mutant with nine amino acids deleted in the GluA2 protein, which resulted in specific accumulation of the GluA precursor. The deleted amino acids constitute a well-conserved sequence (LVYIIQGRG) in glutelins and all residues in this motif are necessary for ER export of GluA2. Immunoelectron microscopy and stable transgenic analyses indicated that proglutelins with deletion of this motif misassembled and aggregated through non-native intermolecular disulfide bonds, and were deposited in ER-derived protein bodies (PB-Is), resulting in conversion of PB-Is into a new type of PB. These results indicate that the conserved motif is essential for proper assembly of proglutelin. The correct assembly of proglutelins is critical for their segregation from prolamins in the ER lumen, which is essential for enabling the export of proglutelin from the ER and for the proper formation of PB-Is. We also found that the interchain disulfide bond between acidic and basic subunits is not necessary for their assembly, but it is required for proglutelin folding.